Recurrent VGLL3 fusions define a distinctive subset of spindle cell rhabdomyosarcoma with an indolent clinical course and striking predilection for the head and neck - Agaimy, Abbas; Dermawan, Josephine K.; Leong, Iona; Stöhr, Robert; Swanson, David; Weinreb, Ilan; Zhang, Lingxin; Antonescu, Cristina R.; Dickson, Brendan C. (Genes Chromosomes & Cancer, 2022)
The mammalian Vestigial-like (VGLL) transcriptional cofactor family of proteins VGLL1-4 has recently emerged as an important player in the tumorigenesis of diverse neoplasms. The role of VGLL3 in soft tissue tumors is exemplified by its amplification in myxoinflammatory fibroblastic sarcoma and its rearrangement (fused to CHD7, CHD9, or MAMLD1) in hybrid schwannoma-perineurioma. This study characterizes a distinctive low-grade myogenic neoplasm with a striking predilection for the head and neck, characterized by VGLL3 fusions. The study includes five males and one female patient, aged 30–71 years (median, 56). Three tumors originated in the tongue, with one case each in the nasopharynx, oral cavity, and oropharynx. The VGLL3 fusion partners included TCF12 (n = 3), EP300 (n = 2), and PPARGC1A (n = 1). The tumor size range was 0.8–1.6 cm (all, but one, was <1 cm). Histologically, all tumors displayed bland spindle to ovoid cells arranged into vague fascicular and diffuse patterns. Mitotic activity ranged from 1 to 7 per 10 HPFs. Five tumors were muscle-centered and infiltrative, and one was centered beneath nasopharyngeal mucosa. Immunohistochemistry revealed consistent expression of desmin (diffuse in four and patchy in two cases) associated with patchy smooth muscle actin expression (4/6), and focal reactivity for myogenin (5/6) and myoD1 (1/3). All patients were managed surgically; one patient each received adjuvant radio- or chemotherapy. Three patients with follow-up were without disease at 8, 19, and 60 months and one was alive with unknown disease status at 24 months. All VGLL3 fusions were in-frame and involved exon 2, fused with either TCF12 exon 16, EP300 exon 31, or PPARGC1A exon 5, respectively. This series characterizes a distinctive subset of spindle cell rhabdomyosarcoma (RMS) with a predilection for the head and neck in adults, defined by VGLL3 fusions, likely indolent behavior and limited rhabdomyoblastic differentiation. Further delineation of this entity and differentiation from more aggressive molecular subtypes of spindle cell RMS is mandatory to define the most appropriate therapeutic strategy and avoid overtreatment.
CRIS-Team Scopus Importer:2022-08-12
Keywords: EP300; gene fusion; head and neck; PPARGC1A; sarcoma; spindle cell rhabdomyosarcoma; TCF12; VGLL3